Deep Anterior Lamellar Keratoplasty and Phototherapeutic Keratectomy for Management of Thiel-Behnke Corneal Dystrophy. Issue 1 (2017) - Monaco, Gaspare; Scialdone, Antonio; Gari, Mariangela; Messina, Marco; Wilde, Craig; Dua, Harminder S.
Background: To evaluate the outcome of surgical options in the management of Thiel-Behnke corneal dystrophy (TBCD). This is a retrospective case report. Methods: A 52-year-old female with TBCD with a visual acuity of 0.50 LogMAR in both eyes underwent deep anterior lamellar keratoplasty (DALK) in her left eye (LE) and, 8 months later, phototherapeutic keratectomy (PTK) in her right eye (RE). Postoperatively, the presence of recurrence, uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA), central corneal thickness (CCT), and spherical equivalent (SE) were assessed. Spectralis domain anterior segment optical coherence tomography was also performed to evaluate corneal morphology and reflectivity. Results: At 1 year, the LogMAR UCVA and BCVA were +0.80 and +0.24, respectively, in the LE and +0.70 and +0.24 in the RE, respectively. CCT and SE were 741 microns (μm) and +4.25 diopters (D) in the LE, respectively, and 339 μm and +6.00 D in the RE, respectively. The cornea was clear in the LE. There was early recurrence of the TBCD and corneal haze in the RE. Conclusions: The visual outcome of both DALK and PTK were similar for TBCD. No episodes of rejection or recurrence of dystrophy were noted in the eye that underwent DALK. However, postoperative hyperopic shift, persistent haze, and early recurrence were noted after PTK.